2019
DOI: 10.1101/567255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryopreservation ofRosa hybridacv. Helmut Schmidt by PVS2 vitrification method usingin vitrofragmented explants (IFEs)

Abstract: 1415 This is the first report on cryopreservation via PVS2 vitrification method on roses using in vitro 16 fragmented explants (IFEs) as the starting material. The aim of this study is to optimize the efficient 17 plant recovery and regeneration system for cryopreservation of Rosa hybrida cv. Helmut Schmidt 18 using IFEs. Some important parameters have been optimized in this study are the effect of ascorbic 19 acid (0.3 mM) examined separately and in combination at all steps in cryopreservation procedure 20 (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Scavenging these surplus radicals may achieve tolerance to such harmful effects (Halder et al 2018). Published reports have employed antioxidants such as ascorbic acid, glutathione, and melatonin to directly remove the ROS and protect cellular functions, thus improving the chances of survival (Uchendu et al 2013;Uchendu et al 2014;Diengdoh et al 2019;Mubbarakh et al 2019;Khor et al 2020;Soonthornkalump et al 2020). Present ndings showed that melatonin-supplemented during the recovery stage did not accelerate the growth of cryopreserved axillary buds of L. discolor (Fig.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Scavenging these surplus radicals may achieve tolerance to such harmful effects (Halder et al 2018). Published reports have employed antioxidants such as ascorbic acid, glutathione, and melatonin to directly remove the ROS and protect cellular functions, thus improving the chances of survival (Uchendu et al 2013;Uchendu et al 2014;Diengdoh et al 2019;Mubbarakh et al 2019;Khor et al 2020;Soonthornkalump et al 2020). Present ndings showed that melatonin-supplemented during the recovery stage did not accelerate the growth of cryopreserved axillary buds of L. discolor (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Axillary buds were collected for enzyme extraction at various cryopreservation stages adapted from Mubbarakh et al (2019) as follows:…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…In this study, the suspended cells of C. roseus were treated with various concentrations of osmotica and cryoprotective agents, the moderate level was noted to be more efficient in promoting viability and regrowth than the higher levels, very consistent with earlier observation 30 , 31 . Similarly earlier research indicated that the plant vitrification solution 2 (PVS2)—a mixture of compounds containing 30% (w/v) glycerol + 15% (w/v) PEG + 15% (w/v) DMSO + 0.4 M sucrose (osmoticum) added medium improved preservation of cells and promoted culture regrowth 19 , 32 . The extra diffusion/removal of water, however, damages the prospect of survivability and in such a situation, the slow gradual cooling and inclusion of cryoprotective agents like DMSO have been noted to be successful in several investigated plants genera 33 .…”
Section: Discussionmentioning
confidence: 79%
“…Scavenging these surplus radicals may achieve tolerance to such harmful effects [ 65 ]. Published reports have employed antioxidants such as ascorbic acid, glutathione, and melatonin to directly remove the ROS and protect cellular functions, thus improving the chances of survival [ 35 , 36 , 62 , 66 , 67 , 68 ]. Studies describing the protective role of melatonin and enhancement in the recovery of cryopreserved shoot tips of American elm and yam were documented [ 66 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Axillary buds were collected for enzyme extraction at various cryopreservation stages adapted from Mubbarakh et al [ 67 ] as follows: Axillary buds excised from in vitro plants (control); Preculture on medium containing 0.2 M sucrose; Osmoprotection by loading solution; Dehydration with PVS2 for 10 min; Rapid cooling and rewarming; Recovery after 1 day on growth medium with 0.05 µM melatonin (Recovery 1); Recovery after 3 weeks on growth medium with 0.05 µM melatonin (Recovery 2). …”
Section: Methodsmentioning
confidence: 99%